DFT calculations of strain and interface effects on electronic structures and magnetic properties of L10-FePt/Ag heterojunction of GMR applications - Sittichain Pramchu (2018)
© 2018 Author(s). In this work, density functional theory (DFT) was employed to investigate the effect of strain and interface on electronic structures and magnetic properties of L10-FePt/Ag heterojunction. Two possible interface structures of L10-FePt(001)/Ag(001), that is, interface between Fe and Ag layers (Fe/Ag) and between Pt and Ag layers (Pt/Ag), were inspected. It was found that Pt/Ag interface is more stable than Fe/Ag interface due to its lower formation energy. Further, under the lattice mismatch induced tensile strain, the enhancement of magnetism for both Fe/Ag and Pt/Ag interface structures has been found to have progressed, though the magnetic moments of "interfacial" Fe and Pt atoms have been found to have decreased. To explain this further, the local density of states (LDOS) analysis suggests that interaction between Fe (Pt) and Ag near Fe/Ag (Pt/Ag) interface leads to spin symmetry breaking of the Ag atom and hence induces magnetism magnitude. In contrast, the magnetic moments of interfacial Fe and Pt atoms reduce because of the increase in the electronic states near the Fermi level of the minority-spin electrons. In addition, the significant enhancements of the LDOS near the Fermi levels of the minority-spin electrons signify the boosting of the transport properties of the minority-spin electrons and hence the spin-dependent electron transport at this ferromagnet/metal interface. From this work, it is expected that this clarification of the interfacial magnetism may inspire new innovation on how to improve spin-dependent electron transport for enhancing the giant magnetoresistance (GMR) ratio of potential GMR-based spintronic devices.